Perbandingan Konsep Sistem Lembaga Keuangan Sosial Syariah : Bank Wakaf Mikro, Baznas Microfinance Desa, dan Bank Infak - Alimin, Alimin; Fahlefi, Rizal; Shabri, Husni; Zulkifli, Zulkifli (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This research aims to analyze the comparison of the concept of the operational system of Islamic Social Financial Institutions such as the Micro Waqf Bank, Baznas Microfinance Village, and Infak Bank. The research method uses qualitative Conceptual Comparison Method. Data collection techniques using interviews and documentation. The results showed that the system concepts of three Indonesian Islamic social financial institutions are purely social from the aspects of status as a social institution, funding, financing, and distribution, and have many operational system similarities. However, there are differences in the sources of capital in the form of alms, zakat, waqf, general donations, and CSR which have become the responsibility of the company. In terms of type, the three institutions are classified as ethical banks or non-bank Islamic ethical financial institutions because they emphasize the purpose of their activities on outcomes and impact rather than profit at all. In terms of the cash waqf theory of capital resilience, the three institutions are less efficient from the aspect of business sustainability, because the amount is at risk of decreasing and will always depend on donations, where the funds are channeled to poor businesses that are at risk of inability to repay loans. The researcher recommends a commercial social financial institution model that is commercial in seeking profit, but social in profit distribution